Why Replication Matters: The role of psychological factors in the decision to replicate in Psychophysiology - Silva, C.; Frade, S.; Arriaga, P. (XXI PhD Meeting in Psychology, 2026)
Over the last decade, the so-called “replication crisis” has raised concerns about the robustness and reproducibility of published findings across several fields, with large-scale initiatives facing challenges in replicating studies, particularly in psychology, where success rates were substantially lower than expected. This crisis contributed to discussions about research practices and underscored that replication should be regarded not merely as a corrective response, but as a central pillar of scientific progress. Despite its recognized importance, replication remains undervalued, inconsistently practiced, and subject to multiple barriers. Prior studies on replication have focused on institutional and career-related obstacles, yet psychological factors (e.g., fear of criticism, failure-related anxiety) may also influence researchers’ decisions to engage in replication and remain underexplored. In the present work, we first provide a synthesis of the literature on replication, followed by an empirical study that will examine how perceived barriers and psychological factors relate to researchers’ motivations and intentions to replicate studies in psychology. We expect that higher perceived barriers and lower familiarity with replicability will be associated with stronger negative emotions, which in turn will be linked to lower intentions to conduct replication studies and reduced likelihood of publishing the results. Conversely, lower perceived barriers and greater familiarity with replicability are expected to be associated with more positive emotions, higher intentions to replicate, and a greater likelihood of publishing the results. By integrating psychological perspectives, our study aims to advance knowledge in psychology and metascience by examining factors associated with engagement in scientific replication in researchers’ decision-making processes.